3(y-9)4=-2y

Simple and best practice solution for 3(y-9)4=-2y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(y-9)4=-2y equation:


Simplifying
3(y + -9) * 4 = -2y

Reorder the terms:
3(-9 + y) * 4 = -2y

Reorder the terms for easier multiplication:
3 * 4(-9 + y) = -2y

Multiply 3 * 4
12(-9 + y) = -2y
(-9 * 12 + y * 12) = -2y
(-108 + 12y) = -2y

Solving
-108 + 12y = -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
-108 + 12y + 2y = -2y + 2y

Combine like terms: 12y + 2y = 14y
-108 + 14y = -2y + 2y

Combine like terms: -2y + 2y = 0
-108 + 14y = 0

Add '108' to each side of the equation.
-108 + 108 + 14y = 0 + 108

Combine like terms: -108 + 108 = 0
0 + 14y = 0 + 108
14y = 0 + 108

Combine like terms: 0 + 108 = 108
14y = 108

Divide each side by '14'.
y = 7.714285714

Simplifying
y = 7.714285714

See similar equations:

| 4z-43=2z+80 | | 4(2z-8)-(z-9)=8(8-7z) | | -5+36=7 | | -5g+1.2=-18.8 | | 10x-186=90-2x | | 7(k+9)=9(k-5)-14 | | 3y=4(x+6) | | -(5x+8)+12=17+17 | | 4f+2= | | -7j+62=-2g+12 | | 11b^2-71b-42=0 | | 5-c-10-5c-2=8 | | M=-4m+15 | | -4x-6x=20 | | Y=-1x+5 | | 8x+x-5=40 | | .4x+.4=g | | 1.4x-3.5=0.6x-2.54 | | 4+7f=f+16 | | 1+5x=7+3x | | (2x+3)(x+k)=0 | | 3(4r-5)-36= | | 4+7f=x+16 | | 8x+1.2=-70 | | 30n-40=-41+3n | | 4-7f=f+16 | | .25x-3=x+8 | | 2r-(3.1)=1.7 | | 8x-3=-9 | | .4x+.06(30)=9.8 | | 5x+6=3(x-8) | | 2*x+1=22 |

Equations solver categories